A Brief Response to Meek, Morris, and Mullins - Johnson, Dru (Philosophia Christi, 2024)
This response to the symposium participants includes deep appreciation for their engagement with Biblical Philosophy: A Hebraic Approach to the Old and New Testaments. Esther Meek, Dolores Morris, and R. T. Mullins offer helpful insights, correctives, and questions about Biblical Philosophy. They also extended the project to shed light in other philosophical and theological domains. Ultimately, Dru Johnson asks how much of a revolution in philosophical style is required if one were to appropriate the fullness of his suggestions in the book.